Medicaid expenditures for children living with smokers - Levy Douglas E; Rigotti Nancy A; Winickoff Jonathan P (BMC, 2011)
Abstract Background Children's exposure to secondhand smoke is associated with increased morbidity. We estimated Medicaid expenditures for children living with smokers compared to those living with no smokers in the United States. Methods Data were overall and service-specific (i.e., inpatient, ambulatory, emergency department, prescription drug, and dental) annual Medicaid expenditures for children 0-11 years old from the 2000-2007 Medical Expenditures Panel Surveys. Smokers' presence in households was determined by adult respondents' self reports. There were 25,835 person-years of observation. We used multivariate analyses to adjust for child, parent, and geographic characteristics. Results Children with Medicaid expenditures were nearly twice as likely to live with a smoker as other children in the U.S. population. Adjusted analyses revealed no detectable differences in children's overall Medicaid expenditures by presence of smokers in the household. Medicaid children who lived with smokers on average had $10 (95% CI $3, $18) higher emergency department expenditures per year than those living with no smokers. Conclusions Living with at least one smoker (a proxy for secondhand smoke exposure) is unrelated to children's overall short-term Medicaid expenditures, but has a modest impact on emergency department expenditures. Additional research is necessary to understand the relationship between secondhand smoke exposure and long-term health and economic outcomes.